Dynamic Panel Data Modeling of Regional Economic Growth Using Generalized Method of Moments Arellano-Bond Approach - Fuad Muhajirin Farid; Yeni Rahkmawati; Selvi Annisa; Muhammad Riza Hafizi (Jurnal Varian, 2026)
South Kalimantan’s regional economy remains strongly dependent on the mining and quarrying sector, raising concerns about growth persistence and structural dependence. While numerous studies have examined regional economic growth, they predominantly relied on static panel models that fail to capture dynamic adjustments and potential endogeneity issues inherent in macroeconomic. The objective of this research is to analyze the dynamic relationship between exogenous variables and economic growth in South Kalimantan and to address gaps in previous research. The method employed in this study is the Arellano–Bond Generalized Method of Moments (GMM), using balanced panel data from 12 regencies/cities in South Kalimantan over the period 2017–2025. The results indicate that lagged economic growth, the mining and quarrying sector, and realized investment have a significant and positive effect on regional economic growth. The short-run elasticity further indicates that mining and quarrying generate a stronger growth response than realized investment, confirming the continued dominance of extractive activities in the regional economy. These findings imply that South Kalimantan’s growth is dynamic but remains structurally dependent on resource-based sectors. Therefore, regional governments should optimize mining contributions by strengthening environmental governance, accelerating economic diversification, improving investor-related public services, and strengthening linkages among investment, local labor absorption, and MSME development.